'A disguised Liberal vote'? – third-party voting and the SNP under Gordon Wilson in Dundee during the 1970s and 1980s. Issue 3 (3rd July 2019) - Stewart, Thomas A. W.
ABSTRACT: This article inspects the nature of the Scottish National Party and its place in the breakdown of the two-party system across the United Kingdom in the 1970s and 1980s. This is achieved through an examination of the SNP's approach in the small city of Dundee, where the party enjoyed a sustained period of success. It highlights the commonalities between the SNP and the Liberals in the 1970s and SDP-Liberal Alliance in the 1980s. The Nationalists adopted a similar third-party role in Dundee, centring their approach on their moderate politics rather than solely on the issue of self-government. The party's effectiveness in pursuing this approach allowed it to hold on to the Dundee East constituency from 1974 to 1987, until ideological changes affecting the national party made it increasingly impossible to hold firm to this strategy. Nonetheless, this study makes clear that the rise of Scottish Nationalism was a part of a process of British-wide political change, and should not be understood in isolation from the rest of the country.